Childhood parental behaviour and young people's outcomes - John Ermisch; Marco Francesconi; David J. Pevalin (University of Essex, Institute for Social and Economic Research (ISER), 2002)
This paper estimates the relationship between several outcomes in early adulthood (education, inactivity, early birth, distress and smoking) and experiences of life in a single-parent family and with jobless parent(s) during childhood. The analysis is performed using a special sample of young adults, who are selected from the first nine waves of the British Household Panel Survey (1991-1999) and can be matched with at least one parent and one sibling over the same period. This sample allows us to estimate the relationship of interest using sibling differences. We also use another sample of young adults from the BHPS, matched to at least one parent, to estimate more conventional level models and compute nonparametric bounds and point estimates. The estimates based on sibling differences require weaker assumptions (as compared to the assumptions imposed by nonparametric estimators under conditional independence and level estimators) for the identification of the effects of family structure and parental joblessness on the outcomes under analysis. We find that: (i) experiences of life in a single-parent family and with jobless parents during childhood are usually associated with disadvantageous outcomes for young adults;(ii) the effect of family structure is in general significantly greater (in absolute value) than the effect of parental worklessness; (iii) most of the unfavourable outcomes are linked to an early family disruption, when the child was aged 0-5, whereas the timing of parental joblessness during childhood has more complex effects, with different outcomes being more strongly influenced by parental worklessness at different developmental stages.
Keywords: 330